Clinical outcomes of patients with diabetes mellitus treated with Absorb bioresorbable vascular scaffolds: a subanalysis of the European Multicentre GHOST‐EU Registry. Issue 3 (25th October 2017) - Capranzano, Piera; Capodanno, Davide; Brugaletta, Salvatore; Latib, Azeem; Mehilli, Julinda; Nef, Holger; Gori, Tommaso; Lesiak, Maciej; Geraci, Salvatore; Pyxaras, Stelios; Mattesini, Alessio; Münzel, Thomas; et al.
Abstract: Background: Data on the clinical performance of bioresorbable scaffolds in patients with diabetes mellitus (DM) are still limited. The present study reported 1‐year clinical outcomes associated with the use of everolimus‐eluting bioresorbable vascular scaffolds (Absorb BVS; Abbott Vascular, Santa Clara, CA) in DM patients. Methods and Results: This was a subanalysis from the GHOST‐EU (Gauging coronary Healing with biOresorbable Scaffolding plaTforms in Europe) multicenter retrospective registry including patients treated with Absorb BVS between November 2011 and September 2014. In this study, a comparative analysis stratified according to DM was performed. The primary endpoint was target lesion failure (TLF), defined as the combination of cardiac death, target‐vessel myocardial infarction (MI) and clinically‐driven target‐lesion revascularization (TLR). A total of 1, 477 patients were treated with 2, 224 Absorb BVS; 381 (25.8%) and 1, 096 (74.2%) patients were with and without DM, respectively. The 1‐year rate of TLF was higher among patients with DM (7.8%) than those without DM (4.3%); the increase in TLF was driven by TLR (6.5% vs. 3.3%, P  = 0.009); no significant differences in cardiac death (1.1% vs. 0.9%, P  = 0.68) and target‐vessel MI (3.1% vs. 2.2%, P  = 0.38) were observed, respectively. Definite/probable scaffold thrombosis rate tended to be higher among patients with DM than those without DM (3.0% vs. 1.7%, P  = 0.14, respectively). Conclusions: Absorb BVS use in patients with DM was associated with increased 1‐year TLF and scaffold thrombosis compared with non‐diabetes patients.